2016
DOI: 10.1080/0284186x.2016.1244356
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal therapy is feasible in elderly anal cancer patients

Abstract: Patients older than 80 years develop anal cancer, but more often marginal tumors. Even in the oldest age group half of the patients can tolerate standard treatment by a combination of radiation and chemotherapy, and obtain a relative survival of 50% after five years. Fragile patients not considered candidates for chemoradiation may be offered radiation or resection to control local disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…We are unable to determine if this was related to toxic effects of treatment or if clinicians planned to deliver lower doses and omit chemotherapy for these patients; because elderly and more comorbid patients did not have higher rates of treatment interruption, we hypothesize the latter is the more likely reason. Although there are conflicting reports as to how older adults tolerate chemoradiation treatment for SCCA, [19][20][21][22][23] and some studies have suggested omission of chemotherapy or reduction in radiation dose/volume might be appropriate, 24,25 guidelines still recommended that older adults be treated similarly to their younger counterparts. 3,4 Therefore, the results of this study highlight the need for audits and quality improvement efforts to ensure that older adults are receiving guidelineconcordant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We are unable to determine if this was related to toxic effects of treatment or if clinicians planned to deliver lower doses and omit chemotherapy for these patients; because elderly and more comorbid patients did not have higher rates of treatment interruption, we hypothesize the latter is the more likely reason. Although there are conflicting reports as to how older adults tolerate chemoradiation treatment for SCCA, [19][20][21][22][23] and some studies have suggested omission of chemotherapy or reduction in radiation dose/volume might be appropriate, 24,25 guidelines still recommended that older adults be treated similarly to their younger counterparts. 3,4 Therefore, the results of this study highlight the need for audits and quality improvement efforts to ensure that older adults are receiving guidelineconcordant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients had a 5 year OS of 60.8% compared to 74.6% in younger patients, however this was not statistically signi cant, nor was there a signi cant difference in LRC. Although a lack of signi cant difference in OS is unexpected (21), this outcome is most probably due to a to small sample size.…”
Section: Discussionmentioning
confidence: 94%
“…Older patients had a 5 year OS of 60.8% compared to 74.6% in younger patients, however this was not statistically significant, nor was there a significant difference in LRC. Although a lack of significant difference in OS is unexpected [ 22 ], this outcome is most probably due to a to small sample size.…”
Section: Discussionmentioning
confidence: 99%